LANGUAGE IS THE BASIS OF THE CULTURE OF EVERY NATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
In this article, the work on the introduction of the Uzbek language as a state language and the increase of the position of the Uzbek language among world languages, as well as the practical results of these reforms are explained scientifically.